 # if y= 1+(a/x-a)+(bx/(x-a)(x-b))+(cx^2/(x-a)(x-b)(x-c)) than show that dy/dx=y/x[(a/a-x)+(b/b-x)+(c/c-x)].............

11 years ago

[a/(x-a)]+1=x/(x-a)
[bx/(x-b)(x-c)]+x/(x-a)=x/(x-a)[b/(x-b)+1]=x2/(x-a)(x-b)
So y={cx^2/ (x-a) (x-b) (x-c)} +x2/(x-a)(x-b)=x2/((x-a)(x-c))[c/(x-c)+1]
y=x3/(x-a)(x-b)(x-c)
logy=3logx-log(x-a)-log(x-b)-log(x-c)
y1/y=3/x+1/(a-x)+1/(b-x)+1/(c-x)
y1/y=[1/x-1/(x-a)]+[1/x-1/x-b]+[1/x-1/x-c]=1/x ( a/a-x + b/ b-x+ c/c-x)

Please feel free to ask your queries here. We are all IITians and here to help you in your IIT JEE preparation.

All the best.

Win exciting gifts by answering the questions on Discussion Forum. So help discuss any query on askiitians forum and become an Elite Expert League askiitian.

Sagar Singh

B.Tech, IIT Delhi

11 years ago

y = 1 + a/(x-a) +bx/(x-a)(x-b) + cx2/(x-a)(x-b)(x-c)

breaking into different  functions

y = 1 +    f(x)1  +       f(x)2       +        f(x)3

f(x)1=a/(x-a)    ,        f(x)2 =bx/(x-a)(x-b)   &   f(x)3 =cx2 /(x-a)(x-b)(x-c)

now

dy/dx= d/dx(1) + d/dx(f(x)1) +d/dx(f(x)2) +d/dx(f(x)3) ....................................1

now separatly differentiatiating f(x)1 , f(x)2  , f(x)3  by taking log

d/dx[log(f(x)1)]  =  d/dx(loga/x-a)

d/dx(f(x)1/f(x)1 = d/dx(loga - log(x-a) )

d/dx(f(x)1)=(-1/x-a)(f(x)1

d/dx(f(x)1) =    -a/(x-a)2

now separatly differentiate each of these and put in eq 1 ,u will get the required result